Effects of Force Account Method on Procurement Process Compliance in Construction Projects - Mwalukasa, Boniface E; Sallwa, Alfred A (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
The effective and efficient use of resources by public organizations through the force account procurement method lowers the costs of various projects, enhancing the performance of the construction projects undertaken by Local Government Authorities. Despite the benefits obtained from the use of force accounts by procuring entities, there are still challenges facing its implementation in terms of value for money. The study is guided by Resource-based View. A Cross-sectional survey design was employed; Simple random sampling was used to select a sample of 116 secondary schools using force account. Primary data was collected using structured questionnaires and interviews, while secondary data was collected through a documentary review. Quantitative data were analyzed using descriptive statistics to compute percentages and means of school respondents, and Multiple Regression was used for inferential statistics analysis. Qualitative data analysis was conducted using NVivo through Thematic analysis. The findings demonstrate the use of force account method has a positive and significant effect on procurement process compliance. However, secondary schools using the force account method face several challenges, including a lack of qualified personnel, difficulty in achieving intended quality, delay in delivery, inexperienced human resources to run and manage huge construction projects, poor record keeping, poor supervision, and top management interference. The study recommends capacity-building training for all force account users, a maximum threshold amount for force account usage, competent project implementation teams, or supervisors based on profession, expertise, and experience and the enforcement of ethical practices in procurement projects. Keywords: Force account, local government authorities, value for money, compliance.